2011
DOI: 10.1371/journal.pone.0014661
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ Sensitizes Neuroblastoma Cells to L-Buthionine-Sulfoximine and Etoposide Inducing Reactive Oxygen Species Overproduction and DNA Damage

Abstract: Neuroblastoma is a type of pediatric cancer. The sensitivity of neuroblastoma (NB) cancer cells to chemotherapy and radiation is inhibited by the presence of antioxidants, such as glutathione (GSH), which is crucial in counteracting the endogenous production of reactive oxygen species (ROS). We have previously demonstrated that cells depleted of GSH undergo apoptosis via oxidative stress and Protein kinase C (PKC) δ activation. In the present study, we transfected PKCδ in NB cells resistant to oxidative death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…In accordance with other studies, 20 we have recently reported that etoposide causes DNA damage and an overproduction of reactive oxygen species (ROS), 21 which have been demonstrated to mediate both cell damage and biological functions. 22 In this regard, herein we show that etoposide induces a dose-dependent increase in the levels of the proapoptotic PKCδ 23 and a parallel decrease of PKC α , the antiapoptotic isoform.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with other studies, 20 we have recently reported that etoposide causes DNA damage and an overproduction of reactive oxygen species (ROS), 21 which have been demonstrated to mediate both cell damage and biological functions. 22 In this regard, herein we show that etoposide induces a dose-dependent increase in the levels of the proapoptotic PKCδ 23 and a parallel decrease of PKC α , the antiapoptotic isoform.…”
Section: Discussionsupporting
confidence: 89%
“…However, given that PKCs are upstream molecules in the ROS signaling pathway leading to DNA damage and apoptosis, 21, 25, 26 it is important to identify the downstream mediators of the NB response to etoposide and we show that etoposide induces the activation of Akt and MAPKs (i.e. JNK, and p38).…”
Section: Discussionmentioning
confidence: 81%
“…Unlike , is commonly expressed (Zeidman et al, 1999b), yet again, transfection studies with full-length, catalytically inactive, or active PKC variants have revealed a pro-apoptotic role (Schultz et al, 2003;Schultz & Larsson, 2004). A major role of PKC in the sensitization of NB cells (SH-SY5Y and SK-N-BE(2C)) to etoposide (Marengo et al, 2011) was just recently described, validating similar observations in other cell types (Griner and Katanietz, 2007). The function of aPKCs in NB differentiation is not clear at present, except recent indications that inhibition of PKC has pro-apoptotic, and antiproliferative effects (Pilai et al, 2011).…”
Section: Aspects Of Pkc Regulation In Neuroblastoma Differentiation 2supporting
confidence: 58%
“…However, molecular signaling of BSO-induced apoptosis is poorly understood, and, recently, it has been demonstrated that in different leukaemia and lymphoma cells, the death receptor-mediated apoptotic pathway, induced by arsenic trioxide plus BSO, is triggered via JNK activation [58]. Moreover, in neuroblastoma cells susceptible to BSO treatment, DNA damage and apoptosis was triggered via PKC- δ activation and ROS production [59, 60]. …”
Section: Gsh Depletion As An Experimental Approach To Sensitize Tumentioning
confidence: 99%